Analisis Kesalahan Penggunaan Bahasa Indonesia Dalam Pembelajaran Ppkn Pada Mahasiswa Hukum UIN Stambuk 2022 - Martua Felix Jonatan Simanullang; Bella Ayu Anzalia; Pingky Monica Hasugian; Halimah Halimah; Hendra Kurniawan (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Analysis of errors in the use of Indonesian in the learning of UIN Law Students is an important study that focuses on how students use written and spoken Indonesian in academic and learning contexts. Indonesian is the official language and language of instruction in education in Indonesia. Good and correct mastery of Indonesian is very important for students to be able to convey ideas, arguments and analyzes clearly and effectively, especially in fields of study such as those that require a deep understanding of citizenship concepts and Pancasila values. This research uses qualitative methods with a case study approach. The focus of this research is to explore the perspectives, experiences and views of UIN Law students. Analysis of errors in the use of Indonesian in the context of higher education, especially in learning Pancasila and Citizenship Education (PPKn), is an important topic for identifying and improving the quality of students' language.